An Evaluation of the ACEP Guideline for Mild Head Injuries in Taiwan. Issue 2 (March 2017) - Hsiao, KY; Li, WC; Chang, CH; Lin, MHC; Yang, JT; Wang, PC; Chen, KH
Introduction: Traumatic brain injury (TBI) is an important issue in the emergency department. In the United States, the American College of Emergency Physicians (ACEP) published clinical guideline to select patients with mild head injuries for head computed tomography (CT) scans in 2008. The aim of this study was to identify the possible benefits of compliance with these guidelines for mild head injury patients in Taiwan. Method: This was a secondary analysis on our previous study published for association of hypertension and head injuries. In our previous study, we collected data about 1290 patients with head injuries who received brain CT scans in the emergency department from September 2012 to August 2013 for a study regarding the association between head injury and hypertension. In present study, we subjected this data to further analysis to try to validate the ACEP clinical policy for mild head injuries. Results: Of these 1, 290 patients, 154 were found to have brain haemorrhage on the initial brain CT scan, and 5 were in need of neurosurgical intervention. A total of 859 patients met the ACEP guideline criteria, and 117 of these had brain haemorrhages. The sensitivity and specificity of the ACEP guideline to predict brain haemorrhage were 75.97% (95% confidence interval [CI], 68.44% to 82.48%) and 34.68% (95% CI, 31.91% to 37.53%), respectively. In predicting neurosurgical intervention, the sensitivity and specificity of the guideline were 100% (95% CI, 47.82% to 100%) and 33.54% (95% CI, 30.96% to 36.2%), respectively. Conclusion: Although adoption of the ACEP clinical policy may reduce the number of brain CT scans in mild head injury patients who may need neurosurgical interventions, it is not a good selection tool in Taiwan.